2013
DOI: 10.1089/lap.2013.0028
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Blood Vessel Seals Are Stronger Than Those Made at an Angle

Abstract: Vessel sealing devices effectively produce hemostatic seals with minimal thermal damage, but the strength of seals decreases as vessel diameter increases. Because vessels sealed at an angle to the vessel require a greater functional seal diameter than those sealed perpendicularly to the vessel, it was hypothesized that perpendicular seals would have comparably higher burst pressures. Ex vivo, porcine carotid arteries of nominal diameters of 5, 6, and 7 mm were sealed perpendicularly to and at a 45°angle to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The principle of achieving hemostasis closer to the midline means that vessels are sealed perpendicularly rather than at an angle. Voegele et al . showed that in vessels of more than 5 mm in diameter, sealing at an angle resulted in significantly less burst pressure than did sealing perpendicular to the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of achieving hemostasis closer to the midline means that vessels are sealed perpendicularly rather than at an angle. Voegele et al . showed that in vessels of more than 5 mm in diameter, sealing at an angle resulted in significantly less burst pressure than did sealing perpendicular to the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The AH mode may also be useful when vessels are sealed at an angle. Burst pressure studies show that a 5 mm vessel divided at a 45° angle has an equivalent burst pressure to that of a 7 mm vessel divided perpendicularly 28. In other words, even though the vessel is 5 mm in diameter, the area of seal is equivalent to a 7 mm vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller end effector of Focus+ enables the surgeon to more readily approach, seal, and cut a vessel at a perpendicular angle, which has been shown to provide a stronger seal. 20 The larger jaw aperture not only allows larger tissue bundles to be coagulated and transected, but also provides better dissecting ability by providing greater mechanical advantage of the dual-action jaw provided by the higher ratio of the handle size to the jaw size.…”
Section: Discussionmentioning
confidence: 99%